Digitalizing Islamic Education Management in the Industry 5.0 Era: From Digital Administration to Value-Based Governance - Asdianur Hadi; Ahmad Sukandar (Jurnal Manajemen dan Pendidikan Agama Islam, 2026)
This article examines the digitalization of Islamic education management in the Industry 5.0 era by emphasizing a shift from mere “digital administration” to value-based governance. The focus goes beyond adopting applications; it highlights a deeper transformation in how institutions manage processes, data, services, and decision-making to enhance effectiveness, accountability, and alignment with the broader purposes of Islamic education. The article synthesizes key pillars of transformation, including system integration across academic, financial, and learning services, strengthened data governance, capacity building for human resources, and cultural change management. While digitalization may improve efficiency and transparency, the article also discusses recurring risks such as digital divides, organizational resistance, vendor dependency, and ethical/privacy concerns, along with practical mitigation strategies. The main contribution is a conceptual governance framework that connects service performance indicators with institutional values, enabling digital transformation to remain meaningful, trustworthy, and sustainable rather than purely technical or procedural.